Offshoring Quotas and Strategic Export Subsidies. Issue 7 (28th May 2018) - Bandyopadhyay, Subhayu; Ghosh, Koushik
ABSTRACT: We present an analysis of strategic export subsidization in the presence of exogenous limits on the extent of offshoring that is permissible for a domestic firm. Rather than offsetting a quota's cost-raising effect, the government reduces its optimal strategic subsidy compounding the negative effects on the domestic firm's market share. This double jeopardy of lower subsidies and greater offshoring restrictions must reduce domestic profits as well as domestic welfare. Finally, we show that there is no guarantee that such an offshoring quota will raise domestic employment in the oligopolistic sector, calling into question the efficacy of such a barrier.